PASSAGES OF INSCRIPTION - Trangmar, Susan (Photographies, 2019)
"Passages of Inscription" arises from the film "UNFOUND", commissioned to mark the centenary of the Battle of the Somme which took place during the First World War in 1916. My concern in the making was how my approach to such a historically burdened subject could avoid the closures of institutional historical memory. The landscape of the Somme is framed through a series of durational image and sound episodes eschewing narrative development, and focusing upon incidental details of daily life, seasonal change and industrial presences which encroach upon the Somme cemeteries. Stitched into these episodes are still images of inscriptions on individual grave headstones, requiring constant re-engraving against erosion. This structure is intended to give the viewer "breathing space" to reflect upon the continuous production of multiple histories infused with subjective experience. This essay assembles selected personal writings and commentary, made during the research process, moving between sites connected to the First World War in southern England and the landscape of the Somme. Intertwining text, carved inscription and landscape images the essay proposes that discourses of memorialization are intrinsically subject to interruption, lacunae and illegibility and concludes by suggesting that it is the material process of reinscription which expands contextual reference and significance.